LEGO Batman the movie : DC super heroes unite [videorecording (Blu-Ray)] - Burton, Jon; Goodman, David A., 1962-; Brown, Clancy; Smith, Chris (Christopher Corey); Bloom, Brian, 1970-; Paulsen, Rob, 1956-; Bailey, Laura, 1981-; Willingham, Travis; Schlatter, Charlie; Baker, Troy (Warner Home Video, 2013)
When Bruce Wayne receives the man of the year award, fellow billionaire Lex Luthor becomes jealous and decides to run for President. To create the atmosphere for his type of fear-based politics Lex recruits the Joker to perfect a Black LEGO Destructor Ray which wreaks havoc on Gotham. As Lex destroys Batman's tech, Batman reluctantly turns to Superman for help.